Identiteta in performativnost - Praprotnik, Tadej (Monitor ISH, 2009)
The article deals with the question of speech acts, and is primarily focused on performatives. The concept of performatives also gives a starting point for deeper elaboration of the "status" of (national) identity. The article explores the process of constitution of identity, especially their never-ending character. Of considerable importance is also, of course, the effect of the identification process itself, because it is by their identification that individuals become that which they identified themselves as, there by lending "retroactive" support to the substantiation of ideological mystifications of this kind. In this way, we wish to emphasiye the performative dimension buried in the framework of ideological rituals or discourses.
Keywords: performativnost; identiteta; jezik; Language; narodna identiteta